Study on Key Influencing Factors of Carbon Emissions from Farmland Resource Utilization in Northeast China Under the Background of Energy Conservation and Emission Reduction - Mulin Sun; Yuhao Fu; Mingyao Sun; Run Huang; Yun Teng (Energies)
Under the background of energy conservation and emission reduction, how to rationally and scientifically utilize the non-renewable resources of northeastern farmland is particularly important. In this study, the carbon emission coefficient method is used to select six major carbon sources with energy consumption, including energy consumption in the process of fertilizer production, agricultural machinery use, irrigation, and agricultural waste treatment, to measure the spatial and temporal carbon emissions from the utilization of farmland resources in Northeast China during 2012–2021. A gray prediction model is constructed to predict the carbon emissions from the utilization of farmland resources in the next 10 years, and the logarithmic mean Divisia index model is used to analyze the effects of the various influencing factors on the carbon emissions from farmland utilization. The results show the following: (1) Between 2012 and 2021, carbon emissions from farmland use in Northeast China show a fluctuating development trend of rising and then falling, and the distribution of carbon emissions within the region is characterized by a decreasing trend of “high-middle-low” from the north to the south. (2) Carbon emissions from farmland use in the next 10 years will maintain a gently decreasing trend. (3) The industrial structure of farmland, the level of economic development and the level of urbanization play a contributing role in carbon emissions. The industrial structure of farmland, the level of economic development, and the level of urbanization contribute to carbon emissions from the use of farmland resources. (4) The efficiency of farmland use, the regional industrial structure, and the size of the labor force inhibit the carbon emissions from the use of farmland. This study provides a scientific basis and strategic recommendations for optimizing the use of farmland resources, adjusting the structure of energy use, and realizing the balanced development of land and energy resources under the goal of energy conservation and emission reduction in Northeast China.